The antithrombotic potential of selective blockade of talin-dependent integrin αIIbβ3 (platelet GPIIb–IIIa) activation - Brian G. Petrich; Per Fogelstrand; Anthony W. Partridge; Nima Yousefi; Ararat J. Ablooglu; Sanford J. Shattil; Mark H. Ginsberg (The Journal of Clinical Investigation, 2007)
In vitro studies indicate that binding of talin to the β3 integrin cytoplasmic domain (tail) results in integrin αIIbβ3 (GPIIb–IIIa) activation. Here we tested the importance of talin binding for integrin activation in vivo and its biological significance by generating mice harboring point mutations in the β3 tail. We introduced a β3(Y747A) substitution that disrupts the binding of talin, filamin, and other cytoplasmic proteins and a β3(L746A) substitution that selectively disrupts interactions only with talin. Platelets from animals homozygous for each mutation showed impaired agonist-induced fibrinogen binding and platelet aggregation, providing proof that inside-out signals that activate αIIbβ3 require binding of talin to the β3 tail. β3(L746A) mice were resistant to both pulmonary thromboembolism and to ferric chloride–induced thrombosis of the carotid artery. Pathological bleeding, measured by the presence of fecal blood and development of anemia, occurred in 53% of β3(Y747A) and virtually all β3-null animals examined. Remarkably, less than 5% of β3(L746A) animals exhibited this form of bleeding. These results establish that αIIbβ3 activation in vivo is dependent on the interaction of talin with the β3 integrin cytoplasmic domain. Furthermore, they suggest that modulation of β3 integrin–talin interactions may provide an attractive target for antithrombotics and result in a reduced risk of pathological bleeding.